The effect and possible mitigation of UV radiation on baculoviruses as bioinsecticides - Anggraini, Erise; Hong, Lau Wei; Vadamalai, Ganesan; Kong, Lih Ling; Mat, Mazidah (Society for Indonesian Biodiversity, 2022)
The effect and possible mitigation of UV radiation on baculoviruses as bioinsecticides. Biodiversitas 23: 3721-3735. Indiscriminate use of pesticides has raised concerns over environmental and human health issues. A more environmentally-friendly biological approach to control insect pests is gaining importance. For decades, bioinsecticides based on viruses have been used to protect crops and forests. The viruses belonging to the Baculoviridae family are known to infect insect pests, and hence can be used as biopesticides. Baculoviruses are mostly specific to the host and are not lethal to the non-target organism. However, their usage is limited for field application due to a slow kill speed and sensitivity towards UV irradiation. This review paper discusses the life cycle of baculoviruses, their mode of infection and transmission as well as the influence of UV radiation on the effectiveness of baculoviral insecticides for field application.